Acute Coronary Syndrome A Review - Nagal, Jahnu Bhoj; Upadhyay, Manal; Bang, Swati; Jain, Kavita (Journal of Neonatal Surgery, 2025)
According to studies, ACS is a set of conditions marked by a sudden decrease in BF to the heart, which may result in MI /UN-AN. These conditions are mostly attributable to obstructions in the CA, which may result from ruptured PQ/ TB. Therefore in our review we have discussed about its epidemiology, pathophysiology, diagnosis, pretreatment and treatment aspect for its better understanding....